Cytogenetic characterization of Brycon amazonicus (Spix et Agassiz, 1829) (Teleostei: Characidae) from Caicara del Orinoco, Venezuela - Mariguela, T. C. [UNESP]; Nirchio, M.; Ron, E.; Gaviria, J. I.; Foresti, Fausto [UNESP]; Oliveira, C. [UNESP] (Zoological Inst, 2010)
A cytogenetic analysis by conventional Giemsa staining, silver staining, C-banding, and fluorescence in situ hybridization (FISH) was carried out on Brycon amazonicus from Caicara del Orinoco, Venezuela. The karyotype of this species is characterized by the presence of 2n = 50 chromosomes, a karyotypic formula 22m+14sm+14st, and a fundamental number of 100 chromosomal arms. Nucleolar organizer regions (NORs) and 18S rDNA genes are located in the terminal regions of the long arms of the second pair of subtelocentric chromosomes, corresponding to pair 13. C-banding revealed heterochromatin distribution in only seven chromosome pairs. The largest metacentric pair (number 1) possesses a paracentromeric block equilocally distributed in both chromosome arms, whereas in pairs 12 to 17 positive C band blocks were located in the paracentromeric region of the long arm, close to the centromere. Analysis performed with 5S rDNA gene revealed a terminal site located on the short arm of one small submetacentric chromosome (pair 15) corroborating previous studies with this repetitive gene showing an apparent conservation of 5S rDNA in the genome of these fish species. The data obtained in this study reinforce the chromosomal conservativeness in the species of the genus Brycon, related not only to the macro-chromosomal structure (diploid number, karyotypic formula, and fundamental number), but also to the repeated DNAs, such as heterochromatic regions and ribosomal DNAs. These data will contribute to a better understanding of chromosomal evolution in both Brycon and Characidae fishes.
Keywords: Characidae; C-banding; karyotype; NORs; 18S rDNA; 5S rDNA